Hydrolysis of Methylumbeliferyl Substrate Proxies for Esterase Activities as Indicator for Microbial Oil Degradation in the Ocean: Evidence from Observations in the Aftermath of the Deepwater Horizon Oil Spill (Gulf of Mexico) - Kai Ziervogel; Manoj Kamalanathan; Antonietta Quigg (Journal of Marine Science and Engineering, 2022)
Biological oil weathering facilitated by specialized heterotrophic microbial communities plays a key role in the fate of petroleum hydrocarbon in the ocean. The most common methods of assessing oil biodegradation involve (i) measuring changes in the composition and concentration of oil over time and/or (ii) biological incubations with stable or radio-labelled substrates. Both methods provide robust and invaluable information on hydrocarbon biodegradation pathways; however, they also require extensive sample processing and are expensive in nature. More convenient ways to assess activities within microbial oil degradation networks involve measuring extracellular enzyme activity. This perspective article synthesizes previously published results from studies conducted in the aftermath of the 2010 Deepwater Horizon (DwH) oil spill in the northern Gulf of Mexico (nGoM), to test the hypothesis that fluorescence assays of esterases, including lipase activity, are sensitive indicators for microbial oil degradation in the ocean. In agreement with the rates and patterns of enzyme activity in oil-contaminated seawater and sediments in the nGoM, we found close correlations between esterase activity measured by means of methylumbeliferyl (MUF) oleate and MUF butyrate hydrolysis, and the concentration of petroleum hydrocarbons in two separate laboratory incubations using surface (<1 m) and deep nGoM waters (>1200 m). Correlations between esterase activities and oil were driven by the presence of chemical dispersants, suggesting a connection to the degree of oil dissolution in the medium. Our results clearly show that esterase activities measured with fluorogenic substrate proxies are a good indicator for oil biodegradation in the ocean; however, there are certain factors as discussed in this study that need to be taken into consideration while utilizing this approach.